Probable Entropic Nature of Gravity in Ultraviolet and Infrared Limits—Part I: An Ultraviolet Case - A. E. Shalyt-Margolin (Advances in High Energy Physics)
This work presents a study of the possibility for extending the well-known results of E. Verlinde concerning the entropic nature of gravity to the ultraviolet region (Planck’s energies) and also the derivation of quantum corrections to Einstein Equations.